2014
DOI: 10.4137/bmi.s15918
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyproline, a Serum Biomarker Candidate for Gastric Ulcer in Rats: A Comparison Study of Metabolic Analysis of Gastric Ulcer Models Induced by Ethanol, Stress, and Aspirin

Abstract: Gastrointestinal symptoms are a common manifestation of adverse drug effects. Non-steroid anti-inflammatory drugs (NSAIDs) are widely prescribed drugs that induce the serious side effect of gastric mucosal ulceration. Biomarkers for these side effects have not been identified and ulcers are now only detectable by endoscopy. We previously identified five metabolites as biomarker candidates for NSAID-induced gastric ulcer using capillary electrophoresis–mass spectrometry (CE–MS)-based metabolomic analysis of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Serum hydroxyproline content is an indicator of collagen metabolism or tissue degradation. Previous studies also confirmed that hydroxyproline is decreased during gastric ulceration induced by NSAIDs and showed the increased activity of the collagenase enzyme in gastric ulcer models [40]. 2oxobutyrate was increased in the tissue samples after ulcer induction.…”
Section: Discussionsupporting
confidence: 62%
“…Serum hydroxyproline content is an indicator of collagen metabolism or tissue degradation. Previous studies also confirmed that hydroxyproline is decreased during gastric ulceration induced by NSAIDs and showed the increased activity of the collagenase enzyme in gastric ulcer models [40]. 2oxobutyrate was increased in the tissue samples after ulcer induction.…”
Section: Discussionsupporting
confidence: 62%
“…The decrease in proline and HYP concentrations reflects an increased collagenase activity following a decrease in the collagen level of the stomach tissue (Takeuchi et al, 2013). A previous study (Takeuchi et al, 2014) also reported that HYP is a serum biomarker, which can predict NSAID-induced gastric damage in rats. In the present study, HYP level in G16 was found to be lower than that in other groups after 3 h. Further, it was statistically lower than that in G0 af-ter 9 and 18 h or that in G2 after 18 h and was lower than in all other groups after 36 h. A decrease in HYP was found in G16 (50%) compared to that obtained in G0, whereas this decrease was less severe in the other groups.…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that these changes are due to the activation of collagenase by NSAID-induced mitochondrial depression and by lesions present in the stomach. There is a significant correlation between the changes in HYP levels in the stomach and serum (Takeuchi et al, 2014).…”
Section: Acta Veterinaria Hungarica 67 2019mentioning
confidence: 92%
See 1 more Smart Citation
“…Details of the remaining CE–MS‐based metabolomics applications of the past two years can be found in Table .…”
Section: Applicationsmentioning
confidence: 99%